THE EFFECT OF STATIC STRETCHING CALF MUSCLE TENDON UNIT WITH THERABAND TOWARD RANGE OF MOTION DORSI FLEXION ANKLE ON ELDERLY PERSON - Novi Dwi Jayanti (P3M Universitas 'Aisyiyah Surakarta, 2022)
Background: Aging is a natural process. One problem that often occurs in the elderly is a decrease in the range of motion in the calf muscle tendons, which can interfere with their physical activities. Purpose: Knowing the effect of static stretching calf muscle tendon unit with theraband toward range of motion dorsi flexion ankle on elderly person. Method: Analytical study with a control group design. The sampling technique uses purposive sampling, with 60 respondents: 30 as the treatment group and 30 as the control group. A goniometer measured ROM. Static stretching can be done using theraband. Result: Dependent T-Test (p < 0.05) It means that there is an effect on the treatment and control groups. Independent T-Test (p < 0.05) it means a significant difference between the treatment and control groups. Conclusion: The research results showed a positive influence.Â